Alpha-lipoic acid may ameliorate testicular damage by targeting dox-induced altered antioxidant parameters, mitofusin-2 and apoptotic gene expression - Guzel, Elif Erdem; Tektemur, Nalan Kaya; Tektemur, Ahmet (Wiley, 2021)
In the study, the ameliorating effects of alfa lipoic acid (ALA) against doxorubicin-induced testicular apoptosis, oxidative stress and disrupted mitochondrial fusion were investigated in male rats. Rats were divided into four groups as control, doxorubicin (DOX), DOX + ALA and ALA. A single dose of 15 mg/kg DOX was administered i.p to the DOX and DOX + ALA groups. 50 mg/kg ALA was given to the DOX + ALA and ALA groups by oral gavage every other day. After 28 days, rat testes and serum samples were collected and analysed. Administration of DOX alone caused a decrease in body and relative testicular weights, seminiferous tubule diameter and germinal epithelium thickness, Johnsen's score and serum testosterone levels. DOX treatment led to severe testicular damage such as tubular degeneration, and atrophic tubules. Also, the activities of superoxide dismutase and glutathione peroxidase were reduced, while the level of malondialdehyde was increased in the testis. The mRNA levels of apoptotic-related genes (CASP3, TP53, BAX, BCL2) and apoptotic index were increased, while mitofusin-2 decreased. DOX caused an increase in CASP3 and a decrease in mitofusin-2 immunoreactivities. Treatment with ALA markedly improved all of DOX-induced biochemical, histochemical and molecular alterations in rat testis. Consequently, ALA has a therapeutic role in ameliorating DOX-induced testicular damage in rats.
Keywords: alfa lipoic acid; apoptosis; doxorubicin; male fertility; mitofusin? 2